Comparison of the relative levels of the 3243 (A-->G) mtDNA mutation in heteroplasmic adult and fetal tissues. - Paul M. Matthews; Julian M. Hopkin; R. M. Brown; J Stephenson; David Hilton‐Jones; Garry K. Brown (1994)
In this report, levels of the 3243 A to G mtDNA mutation associated with the mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome were measured in different heteroplasmic tissues of subjects in a kindred including adults with variable clinical phenotypes and a fetus. The relative proportions of mutant mtDNA varied widely (0.03 to 0.67) between identical tissues of the six different subjects and between different tissues of the same subjects. In the one adult for whom sufficient data were available there was an apparent correlation between the distribution of mutant mtDNA and clinical presentation. A woman without neurological symptoms who died prematurely with a cardiomyopathy and lactic acidosis had higher proportions of mutant in heart (0.49, SD 0.02), skeletal muscle (0.56, SD 0.01), and liver (0.55, SD 0.12) than in other tissues studied (for example, kidney, 0.03, SD 0.01). A strikingly different result was found in a 24 week old fetus in whom there was little variation in heteroplasmy in different tissues (average proportion of mutant mtDNA in six tissues, 0.53, SD 0.02). These observations add cardiomyopathy to the growing list of presenting features of the 3243 mtDNA mutation. The unique results from the fetus suggest also that selection pressures acting on either wild type or 3243 mutant mtDNA (rather than variation from replicative segregation of the heteroplasmic mtDNA) may be responsible primarily for the variable levels of 3243 mutant mtDNA in different heteroplasmic tissues of adults.